The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3390/c4020033
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanostructure Curvature Induced from the Rapid Release of Sulfur upon Laser Heating

Abstract: Laboratory-generated synthetic soot from benzene and benzene-thiophene was neodymium-doped yttrium aluminum garnet (Nd:YAG) laser and furnace annealed. Furnace annealing of sulfur doped synthetic soot resulted in the formation of micro-cracks due to the high pressures caused by explosive sulfur evolution at elevated temperature. The heteroatom sulfur affected the carbon nanostructure in a different way than oxygen. Sulfur is thermally stable in carbon up to~1000 • C and thus, played little role in the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Experimental data show that during carbonization, most of the initial oxygen in the raw materials is lost at the beginning of pyrolysis (lower temperature region), and hence the intermediate species formed after oxygen evolution dictate the resulting carbon skeleton structure and thus its ability to graphitize [25]. Unlike oxygen, nitrogen and sulfur are thermally more stable in the carbon scaffold, and hence they affect the carbon structure in a very different way than oxygen [26,27]. They play a limited role in the initial low-temperature carbonization.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental data show that during carbonization, most of the initial oxygen in the raw materials is lost at the beginning of pyrolysis (lower temperature region), and hence the intermediate species formed after oxygen evolution dictate the resulting carbon skeleton structure and thus its ability to graphitize [25]. Unlike oxygen, nitrogen and sulfur are thermally more stable in the carbon scaffold, and hence they affect the carbon structure in a very different way than oxygen [26,27]. They play a limited role in the initial low-temperature carbonization.…”
Section: Resultsmentioning
confidence: 99%
“…These authors showed that carbon nanostructures produced from the nitrogen-containing precursors displayed greater curvature, and they suggested that this was because the presence of nitrogen facilitated pentagon formation. Similarly, recent work by Abrahamson and Vander Wal has shown that annealing of sulphur-doped synthetic soot can result in curvature of the carbon structure, which may be due to the formation of non-hexagonal carbon rings [46].…”
Section: The Effect Of Precursor Chemistry On Graphitizabilitymentioning
confidence: 89%